Muscle-strength-ratios in para-badminton - with special consideration of the trunk muscles - Felder, H.; Geise, F. (Science and Racket Sports VI, 2019)
Since in Badminton / Para-Badminton the entire body (bilaterally and unilaterally) is integrated in the movement pattern, it is of major interest to examine how strength values and ratios are represented in competitive athletes in terms of sports-specific balances or imbalances. Upper and lower body strength and trunk muscle function have been pointed out as important factors to be successful in Para-Badminton competition. Strength and trunk instability due to impairments, disabilities and handicaps can have adverse effects on posture, function and movement. 22 German national para-badminton athletes were examined by performing maximum isometric strength measurement for the muscles (up to 28) that are important for this sport. Especially the trunk musculature was of a high importance. Because of the present study, general strength values are now available for all para-badminton relevant muscles/muscle groups and serve as strength training orientation values and to prevent injuries following muscle imbalances. It has been shown that the trunk musculature plays a key role. This applies not only to preventive considerations, but also badminton-specific movements - agonist-antagonist comparison showed high significant differences between the trunk flexion and trunk extension muscles - Upper and lower body muscles strength ratios (dominant vs non-dominant and agonist vs antagonist) were received